2008
DOI: 10.1186/1471-2407-8-113
|View full text |Cite
|
Sign up to set email alerts
|

Early onset lung cancer, cigarette smoking and the SNP309 of the murine double minute-2 (MDM2) gene

Abstract: The polymorphism SNP309 (rs2279744) in the promoter region of the MDM2 gene has been shown to alter protein expression and may play a role in the susceptibility to lung cancer. The MDM2 protein is a key inhibitor of p53 and several mechanisms of MDM2/p53 interactions are presently known: modulating DNA-repair, cell-cycle control, cell growth and apoptosis. We used 635 Caucasian patients diagnosed with lung cancer before 51 years of age and 1300 healthy gender and age frequency matched population Caucasian cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
(39 reference statements)
4
20
3
Order By: Relevance
“…However, the group of non-smokers was too small for any meaningful statistical estimation (less than 10%). We did not confirm the previously published relationship between MDM2 expression and the gender of the patients [54], although we did discover higher expression levels of COX-2 and hTERT for female patients. The higher expression of those two genes may be a consequence of the different pathways of tumourigenesis and different triggers for the expression of COX-2 and hTERT, or due to potential gender-specific differences.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the group of non-smokers was too small for any meaningful statistical estimation (less than 10%). We did not confirm the previously published relationship between MDM2 expression and the gender of the patients [54], although we did discover higher expression levels of COX-2 and hTERT for female patients. The higher expression of those two genes may be a consequence of the different pathways of tumourigenesis and different triggers for the expression of COX-2 and hTERT, or due to potential gender-specific differences.…”
Section: Discussioncontrasting
confidence: 55%
“…Conversely, only one study linked the 309T allele with the risk in Caucasians, notably in SQ patients and in males (12). The data of the present study suggests that c.309T>G is not associated with the lung cancer risk among the total population, which is in line with numerous epidemiological studies conducted in Caucasians (13,17,18), African-Americans (13) and Asians (14,16,20). A previous meta-analysis study (39) concluded that the association between c.309T>G and lung cancer was statistically significant in Asians, females and never-smokers, but not in Caucasians, males, ever-smokers or among any of the individual histological types.…”
Section: Adjusted or (95% Ci) A -------------------------------------supporting
confidence: 79%
“…In the study, the frequency of the MDM2 309G alleles among the controls was 0.544, which is almost identical to the frequency observed in the Japanese (0.525) (20), Han Chinese of southeast China (0.499) (14) and Korean (0.534) (16) populations; but is significantly higher compared to the Han Chinese of northeast China (0.455) (15), Caucasian (0.346-0.393) (11)(12)(13)18,38) and African-American (0.109-0.112) (13,38) populations (Fig. 1).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations